2012
DOI: 10.1007/s11033-012-1750-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of polymorphisms in the β2-adrenergic receptor gene with essential hypertension in Han Chinese population

Abstract: The β2-adrenergic receptor (β2-AR) gene has been implicated in the pathogenesis of hypertension. However, the results have been conflicting. In this study, we performed a meta-analysis to assess the associations of 46A/G and 79C/G polymorphisms in β2-AR gene with hypertension risk in Han Chinese population. Published literature from PubMed, ISI Web of Science, Embase databases, CNKI, CBM and Wanfang Data were retrieved. Pooled odds ratio (OR) with 95 % confidence interval (CI) was calculated using fixed- or ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Se han llevado a cabo numerosos estudios genéticos sobre estos sistemas; sin embargo, los resultados han sido incongruentes entre poblaciones, lo que evidencia la heterogeneidad de la hipertensión arterial en su etiología genética en las poblaciones continentales (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58).…”
unclassified
“…Se han llevado a cabo numerosos estudios genéticos sobre estos sistemas; sin embargo, los resultados han sido incongruentes entre poblaciones, lo que evidencia la heterogeneidad de la hipertensión arterial en su etiología genética en las poblaciones continentales (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58).…”
unclassified
“…Information was extracted from a total of 5,088 EH cases and 4,467 controls (Table 1 ) (Fujisawa et al, 1997 ; Baba et al, 1998 ; Tonolo et al, 1999 ; Ringel et al, 2000 ; Thomas et al, 2000 ; Wang Y. et al, 2001 ; Ding et al, 2002 , 2009 ; Liang et al, 2004 ; Masuo et al, 2005 ; Tan et al, 2005 ; Guo et al, 2006 ; Chen et al, 2008 ; Zhang et al, 2012 ; Wang et al, 2013 ; Liu et al, 2015 ; Supplementary Table 2 ). Twenty-five papers were obtained through the search process, among which 16 papers were included for the present meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent molecular epidemiology studies revealed that certain genetic variants are associated with susceptibility to hypertension. In particular, polymorphisms of genes, including the leptin receptor, angiotensinogen, cytochrome P450, vascular endothelial growth factor, adrenoceptor, ApoB, bradykinin beta 2 receptor, and apolipoprotein CIII, have been associated with the susceptibility to this disease (Charita et al, 2012;Fowdar et al, 2012;Gu et al, 2012;Hamedian et al, 2012;Li and Liu, 2012;Shin et al, 2012;Tang et al, 2012;Xi et al, 2012b). Similar to variants of other genes in the apolipoprotein family, apoE gene polymorphisms may also contribute to the occurrence of hypertension in various populations.…”
Section: Discussionmentioning
confidence: 99%